2020
DOI: 10.17524/repec.v14i4.2632
|View full text |Cite
|
Sign up to set email alerts
|

Influência da Folga Financeira no Gerenciamento de Resultados nas Cooperativas de Crédito Brasileiras

Abstract: Objetivo: Identificar a influência da folga financeira no gerenciamento dos resultados (GR) nas cooperativas de crédito singulares brasileiras, como uma estratégia de financiamento pré-perdas. Método: A amostra compreende 626 cooperativas de crédito singulares brasileiras no período entre 2000 e 2019 (20 anos). O modelo-base segue o proposto por Maia et al. (2013), com accruals específicos, controladas por variáveis relacionadas ao perfil das operações de crédito e características como tamanho, captação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…After a review of the literature on organizational change, we found that financial slack is a vital factor in reducing risk aversion [23][24][25][26]. Financial slack refers to a company's underutilized and uncommitted financial resources that could be readily employed to meet its organizational goals [27].…”
Section: Introductionmentioning
confidence: 99%
“…After a review of the literature on organizational change, we found that financial slack is a vital factor in reducing risk aversion [23][24][25][26]. Financial slack refers to a company's underutilized and uncommitted financial resources that could be readily employed to meet its organizational goals [27].…”
Section: Introductionmentioning
confidence: 99%